MODEL PELAYANAN PADA DAMPAK KEPUASAN KONSUMEN STUDI EMPERIK PADA PENGELOLAAN BALI MANDARA TOL - I Dewa Nyoman Usadha (Universitas Mahendradatta, 2022)
The purpose of this study is to explain the service model used by the operationalstandard of the manager on the Bali Mandara Toll satisfaction target. Theresearch used a sample of 98 respondents with purposive sampling technique,which aims to determine the respondent's perception of each variable. Theanalysis used includes Descriptive Statistics Test, Data Instrument Test (ValidityTest, and Reliability Test), Classical Assumption Test (Normality Test,Multicollinearity Test, Heteroscedasticity Test), Multiple Linear RegressionAnalysis, Coefficient of Determination, and Hypothesis Testing (t Test and Test).F). From the results of the analysis using multiple regression, it can be seen thatthe variables of service quality, and employee performance, simultaneously havea positive effect on customer satisfaction. From the t-test, the results show thatservice quality and employee performance have a partial significant effect oncustomer satisfaction. Based on the results of the F test, the results of servicequality and employee performance have a significant simultaneous effect oncustomer satisfaction.